Antiulcer effects of Ethyl acetate fraction of Carpolobia lutea leaf - Nwidu, Lucky Lebgosi; Nwafor, Paul Alozie; Vilegas, Wagner [UNESP] (SAGE Publications, 2012)
Carpolobia lutea leaves (CLL) (Polygalaceae) were earlier screened and the antiulcer ethnomedicinal claim established. This article seeks to quantitatively isolate, elucidate the active compounds from most active CLL fraction. Fractionation was by semi-preparative HPLC; the active fraction was subjected to radical scavenging assays (RSA) and quantification of the total phenolic content (TPC) were also executed. Results: Ethyl acetate fraction (EAF) was observed to be the most pharmacologically active antiulcer fraction when screened using acute ulcer models induced in rodents. The EAF demonstrated significant (p < 0.05-0.001) antiulcer activity in various in vivo induced ulceration models by reducing the ulcer index and increasing the preventive ratio. The EAF demonstrated > 70% in TPC and < 20 % in RSA. Cinnamic and coumaric acids derivatives were isolated from EAF. Cinnamic acids have been implicated and patented as antiulcer agent. Isolated compounds could in part mediate the observed pharmacological activities which lend credence to its ethnobotanical uses.
Keywords: Carpolobia lutea; Cinnamoyl; Coumaroyl-1-deoxyglucoside; Polygalaceae; Ulcerogenic